PENGEMBANGAN MEDIA PORTER SIMPENAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V UPT SD NEGERI NGROJO - Dyah Farisma Septya Ningrum; Novialita Angga Wiratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is a type of Research and Development (R&D) aimed at producing an interactive learning media called Porter Simpenan (Interactive PowerPoint on the Digestive System) to improve the learning outcomes of fifth-grade students at UPT SD Negeri Ngrojo in the IPAS subject, focusing on the human digestive system. The main problem identified was the low student achievement due to the use of conventional and less engaging learning media. Observations, teacher interviews, and student questionnaires revealed that students had difficulty understanding the digestive system's organs and processes and were less active in learning. The development model used was 4D (Define, Design, Develop, Disseminate). The Define stage involved analyzing needs, student characteristics, and learning material. The Design stage focused on planning the media. In the Develop stage, the media underwent expert validation (media, content, language) and was tested for practicality and effectiveness. The product was tested on 33 students. Validation results showed the media was highly valid, with expert scores of 84% (media), 82% (content), and 84% (language). It was also very practical, with teacher and student questionnaire scores of 94% and 95.27%, respectively. The media effectively improved learning outcomes, as the average pretest score increased from 62.3 to 90.9 in the posttest, with an N-Gain of 0.8 (high category). Equipped with menus, images, and evaluation through Google Forms, Porter Simpenan is proven to be valid, practical, and effective for IPAS learning